Athletes` perceptions towards genetic testing - an explorative qualitative study among endurance athletes and their coaches - Konopka, M. J.; Leerschool, A. R.; Gopalakrishna, G.; Wesselius, A.; Rietjens, G.; Zeegers, M. P. (International Journal of Sports Science and Coaching, 2025)
There is growing interest among professional athletes and their support staff in utilising genetic testing to enhance sports performance. However, the perceptions of athletes and coaches regarding genetic testing for training purposes remain largely unexplored. To address this gap, the present interview study investigated the perceptions of athletes and coaches towards genetic testing. Sixteen professional cyclists and triathletes (and their five coaches) participated in semi-structured online interviews after having received their genetic test results. The in-depth interviews were video-recorded, transcribed, translated, and analysed using reflexive thematic analysis by two independent researchers in MAXQDA. Positive perceptions were mainly linked to the potential added value of genetic testing for sports, the importance of counselling, and the necessity for further research. Negative perceptions were mainly linked to incorrect interpretations and conclusions, the use of genetic tests for talent selection, the reliability and usability of results, confirmation bias, fear of stigma, privacy concerns, and costs. Overall, there is a positive perception towards genetic testing among athletes and coaches, emphasising its potential to personalise training programmes. Although some participants highlighted the risks and limitations associated with genetic testing, these concerns were less common. It is suggested that counselling should accompany genetic testing to help athletes and coaches comprehend both the limitations and potential benefits of genetic testing.